Sie sind auf Seite 1von 6

Solutions of Bessel’s Differential Equation

Bessel’s Equation:

x 2 y + xy + (x 2 ν 2 )y = 0,

(1)

where is ν is any real number. Clearly x = 0 is a regular singular point. Let

y(x) =

r=0

a r x r+m , a 0

= 0.

Substitution of (2) into (1) leads to

r=0

r=0

a r (r + m)(r + m 1)x r+m +

r=0

a r x r+m+2 ν 2

r=0

a r x r+m = 0.

a r (r + m)x r+m +

(2)

(3)

Equating the coefficient of x m [least power of x] leads to the indicial equation

m 2 ν 2 = 0.

(4)

The exponents are m = ν and m = ν. Again equating the coefficients of x m+1 , x m+2 to

zero and simplifying, we arrive at the following equations:

a 1 [(m + 1) 2 ν 2 ] = 0,

(5)

a 2 [(m +

2) 2

ν 2 ] =

a 0 .

(6)

The coefficient of a 1 becomes (2ν + 1) when m = ν and (2ν + 1) when m = ν. This,

= ± 1 2 . In the similar

in turn, implies that a 1 = 0 for ν

manner, we may infer that

= ±1/2 and a 1 is arbitrary for ν

a 2 =

[(m + 2) 2 ν 2 ] , ν

a

0

= ±1.

(7)

Note that the equation (6) is inconsistent for ν = ±1 due to our assumption that a 0

This suggests that the second linearly independent solution contains the logarithmic term

for the cases ν = ±1. Equating the coefficient of x m+r , r 2 to zero and solving for a r ,we

have

(8)

= 0.

a r2

a r =

[(r + m) 2

ν 2 ] , r 2.

1

This formula is valid for ν

= ± 2 r . Now we consider the following three cases:

(i)Exponents are distinct and Difference of exponents is not an integer [i.e. 2ν is not an

integer]

(ii)Exponents are equal [i.e. ν = 0]

(iii) Exponents are distinct and differ by an integer [i.e. 2ν is a non-zero integer]

We find two linearly independent solutions of (1) in each of the above said cases.

Case (i): 2ν is not an integer

Recall that a 1 = 0 [see the discussion above (7)]. Equations (7)-(8) lead to

a 2

a

a

4

5

=

=

=

··· .

(m + 2) a 0 2 ν 2 , a 3 = 0, a 0

(1) 2

0, a 6 = (1) 3

[(m + 2) 2 ν 2 ][(m + 4) 2 ν 2 ] ,

a 0

[(m + 2) 2 ν 2 ][(m + 4) 2 ν 2 ][(m + 6) 2 ν 2 ] ,

(9)

Thus

y(x; m)

=

a 0 x m

1

1

[(m + 2) 2 ν 2 ] x 2 +

x

4

[(m + 2) 2 ν 2 ][(m + 4) 2 ν 2 ]

+ ··· .

The general solution in this case is given by

x

6

[(m + 2) 2 ν 2 ][(m + 4) 2 ν 2 ][(m + 6) 2 ν 2 ]

(10)

y(x) = c 1 y(x; ν) + c 2 y(x; ν),

(11)

where the linearly independent solutions y 1 (x) = y(x; ν) and y 2 (x) = y(x; ν) are given by

y 1 (x) = y(x; ν)

=

a 0 x ν 1

x 2

x

4

4(ν + 1) + 4 2 (2!)(ν + 1)(ν + 2)

4 3 (3!)(ν + 1)(ν + 2)(ν + 3) + ··· ,

x

6

2

(12)

y 2 (x) = y(x; ν)

=

a 0 x ν 1

x 2

x

4

4(ν + 1) + 4 2 (2!)(ν + 1)(ν + 2)

4 3 (3!)(ν + 1)(ν + 2)(ν + 3) + ··· .

x

6

(13)

The solution (12) of (1) with a 0 =

ν and is denoted by J ν (x). Thus

2 ν Γ(ν 1 + 1) is called Bessel function of first kind of order

J ν (x) =

r=0

(1) r r! 1 Γ(ν + r + 1) x

2

1

ν+2r

and the general solution of (1) takes the form

(14)

y(x) = c 1 J ν (x) + c 2 J ν (x).

(15)

Case (ii) ν = 0

With ν = 0 and a 0 = 1, equation (10) becomes

y(x; m) = x m 1

1

(m + 2) 2 x 2 +

x

4

(m + 2) 2 (m + 4) 2

(m + 2) 2 (m + 4) 2 (m + 6) 2 + ··· .

x

6

Two linearly independent solutions of (1) are given by y(x; 0) and

y(x; 0) = J 0 (x). In view of the equation (16),

m m=0

∂y

(16)

. Clearly y 1 (x) =

∂y

m

=

x m ln x 1

x

2

(m + 2) 2 +

(m + 2) 2 (m + 4) 2 ···

x 4

+x m

(m + 2) 3 x 2 + ∂m (m + 2) 2

2

1

(m + 4) 2 x 4 − ··· .

(17)

We take m = 0 in (17) to get the second linearly independent solution y 2 (x):

y 2 (x) = m ∂y m=0 = J 0 (x) ln x

+

x 2

4

128 x 4 + ··· .

3

(18)

Case (iii) 2ν is a non-zero integer

Subcase (a) 2ν is an odd integer

In this case smaller exponent gives both the linearly independent solutions of (1). Without

loss of generality, we assume now onwards that ν > 0. For the sake of illustration, we give

a detailed discussion when ν = 1/2. The smaller exponent is ν = 1/2. Equation (5) with

3

ν

equation (8), we get a r for r = 3, 4, 5, · · · in terms of the arbitray constants a 0 and a 1 as

=

1/2 leads to 0 a 1

= 0. This, in turn, implies that a 1 is arbitrary.

In view of the

a 2 = a 0 , a 3 = a 1

2

6 , a 4 =

a 0

24 , a 5 =

a

1

1 2 0 .

120 .

(19)

Thus the general solution solution y of (1) is given by

y(x) = a 0 x 1/2 1 x 2

2

+ x

24 − ··· + a 1 x 1/2 1 x 6 2

4

+

120 − ··· .

x

4

(20)

It is easy to see that the general solution (20) can be written in terms of J 1/2 (x) and J 1/2 (x).

That is,

(21)

y(x) = c 1 J 1/2 (x) + c 2 J 1/2 (x)

It may be noted that the constants a 1 , a 3 , ··· a 2k1 are all zero when 2ν = 2k + 1, where k is

a nonnegative integer and the constant a 2k+1 is arbitrary. Thus, for this case, a 0 and a 2k+1

are arbitrary constants. Further the general solution turns out to be a linear combination of

J ν (x) and J ν (x).

Subcase (b): 2ν is an even integer

The larger exponent gives always one solution. Thus one of the solutions of (1) is y 1 (x) =

J ν (x). The second linearly independent solution of (1) is

where

y 2 (x) = u(x)J ν (x)

u(x) =

dx

2

ν

xJ

(x) .

(22)

(23)

The formulae (22)-(23) are obtained by an application of the method of reduction of order.

Thus the general solution of (1) is

y(x) = c 1 J ν (x) + c 2 u(x)J ν(x) ,

where u(x) is as in (23).

(24)

Alternatively, one may find the second linearly independent solution of (1) using the

For the sake of illustration, we choose ν = 1 and

formula m {(m + ν)y(x; m)} m=ν .

4

Thus, we represent the second

solution of (1) when ν = 1 as a series containing the logarithmic term using the formula

y 2 (x) = m ((m + 1)y(x; m)) m=1 .

construct the second linearly indpendent solution of (1).

The equations (6)-(8) lead to, after using ν = 1, the following formulae for a i :

a 1 = 0, a 2 =

a

0

(m + 3)(m + 1) , a 4 =

a 0 (m + 1)(m +

3) 2 (m + 5) , · · · .

Thus

y(x; m) = x m 1

x

2

(m + 3)(m + 1) +

Multiplying (26) by (m + 1), we obtain

x

4

3) 2 (m + 5) − ··· .

(m + 1)(m +

(m + 1)y = x m (m + 1)

1

(m + 3) x 2 +

x

(m + 5) − ···

4

(m + 3) 2

(25)

(26)

(27)

Then, after simplification, the second linearly independent solution of (1) takes the form

y 2 (x)

=

=

m ((m + 1)y(x; m)) m=1

1

x 1 ln x 2 x 2 +

16 x 4 − ··· + x 1 1 + 4 x 2

1

1

The general solution of (1) is

y(x) = c 1 J 1 (x) + c 2 y 2 (x),

5

64 x 4

+ ··· .

(28)

(29)

where y 2 (x) is given by (28).

Note 1:

If ν is not an integer, then the general solution of Bessel’s equation is given by

y(x) = c 1 J ν (x) + c 2 J ν (x),

where c 1 and c 2 are arbitrary constants.

Bessel’s function of second kind:

Y ν (x) :=

1

sin(νπ) [J ν (x) cos νπ J ν (x)] , ν is not an integer

Y p (x) := lim

νp Y ν (x), p is an integer

5

Note 2:

The general solution of Bessel’s equation for all values of ν is

y(x) = c 1 J ν (x) + c 2 Y ν (x),

where c 1 and c 2 are arbitrary constants.

The Gamma Function:

Γ(x) = 0

t x1 e t dt, x > 0.

Properties of Gamma function:

(i)Γ(1) = 1; Γ(1/2) = π

(ii)Γ(x + 1) = xΓ(x), x > 0

(iii)Γ(n + 1) = n!, when n is a nonnegative integer

Gamma function for negative values of x :

Using the formula (ii),we can define Gamma function for negative values of x as follows.

Γ(x) = Γ(x + 1)

x

Γ(x) = Γ(x + 2)

x(x + 1)

···

, 1 < x < 0

, 2 < x < 0, x

= 1

Γ(x) =

Γ(x + k) x(x + 1)(x + 2) · · · (x + k 1) , x

= 1, 2, ··· − k + 1

It may be observed that Γ(x) becomes infinite as x 0 or a negative integer.

Convention:

1

Γ(N ) = 0, N = 0, 1, 2, ···

THE END

6